2016
DOI: 10.1371/journal.pone.0159413
|View full text |Cite
|
Sign up to set email alerts
|

Liver Stiffness Decreases Rapidly in Response to Successful Hepatitis C Treatment and Then Plateaus

Abstract: Background and AimTo investigate the impact of a sustained virological response (SVR) to hepatitis C virus (HCV) treatment on liver stiffness (LS).MethodsLS, measured by transient elastography (FibroScan), demographic and laboratory data of patients treated with interferon (IFN)-containing or IFN-free regimens who had an SVR24 (undetectable HCV viral load 24 weeks after the end of treatment) were analyzed using two-tailed paired t-tests, Mann-Whitney Wilcoxon Signed-rank tests and linear regression. Two time i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

12
69
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 69 publications
(82 citation statements)
references
References 39 publications
12
69
1
Order By: Relevance
“…In our study we found that patients with advanced inflammation and ALT above 100 U/L had a statistically greater LS change between baseline and FU96, which is consistent with previous studies [40,47,48]. We also found, similarly to Chekuri et al, a positive correlation between the size of LS change and ALT activity between baseline and FU96 [35].…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…In our study we found that patients with advanced inflammation and ALT above 100 U/L had a statistically greater LS change between baseline and FU96, which is consistent with previous studies [40,47,48]. We also found, similarly to Chekuri et al, a positive correlation between the size of LS change and ALT activity between baseline and FU96 [35].…”
Section: Discussionsupporting
confidence: 92%
“…In our group of patients, we found improvement in albumin and ALT levels. However, the level of platelets did not change significantly, which is in contrast to some of the previous studies [35,40]. Probably due to the transient hyperbilirubinemia associated with the treatment (OMB/PRV/rtv ± DSV ± RBV), a statistically significant decrease in the level of bilirubin between baseline and FU24 and FU96 was observed.…”
Section: Discussioncontrasting
confidence: 92%
See 3 more Smart Citations